P53 at the start of the 21st century: lessons from elephants - Haupt, Sue (F1000Res, 2017)
Crucial, natural protection against tumour onset in humans is orchestrated by the dynamic protein p53. The best-characterised functions of p53 relate to its cellular stress responses. In this review, we explore emerging insights into p53 activities and their functional consequences. We compare p53 in humans and elephants, in search of salient features of cancer protection.